Hard, soft и digital skills в современном маркетинге - Фурманова, Диана Вячеславовна (Перспективы развития фундаментальных наук. Т. 5 : сборник научных трудов XVII Международной конференции студентов, аспирантов и молодых ученых, Россия, Томск, 21-24 апреля 2020 г.)
In the present study, we analyzed the main long-term trends in modem marketing and determined core skills that a marketing specialist should have in order to be competitive on the market. We divided these skills into three groups: hard, soft and digital ones. However, we distinguished one more group - heart skills - which is getting cmcially important in modem society. As a result, we got a profde of an ideal specialist that can become successful now and stay like this in the long term. This information can be used by people working or going to work in the marketing field to determine their strengths and competitive advantages, and also to identify their weaknesses and understand what kinds of skills they need to develop.